1999
DOI: 10.1021/ic980990d
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Specular Reflectance Spectra of Fe(β-dtpy)2·4THF:  AD2hModel of Porphyrins

Abstract: Transition metal complexes of β-dtpy (1,2,6,7-tetracyano-3,5-dihydro-3,5-diiminopyrrolizinide) are spectrally similar to metallophthalocyanines (derivatives of porphyrin) but with the advantage of being D 2 h instead of D 4 h so that many degenerate electronic transitions are identifiable separately. We have prepared and characterized Fe(β-dtpy)2·4THF, whose crystal structure allows three spectral polarizations to be measured. We have assigned the visible and ultraviolet transitions that correspond to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
1
8
1
Order By: Relevance
“…Recently, the optical spectrum of FeL 2 was assigned in D 2h symmetry by using polarized specular reflectance measurements on single crystals of its tetrahydrofuran (THF) adduct, FeL 2 ⋅ 4 THF. [6] Well-resolved solid-state optical spectra, in close agreement with the solution spectra, were obtained. Interestingly, it was found that the Q band in this system originates from four different electronic transitions [Q (x) , Q' (y) , R (x) , R' (y) ].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recently, the optical spectrum of FeL 2 was assigned in D 2h symmetry by using polarized specular reflectance measurements on single crystals of its tetrahydrofuran (THF) adduct, FeL 2 ⋅ 4 THF. [6] Well-resolved solid-state optical spectra, in close agreement with the solution spectra, were obtained. Interestingly, it was found that the Q band in this system originates from four different electronic transitions [Q (x) , Q' (y) , R (x) , R' (y) ].…”
Section: Introductionsupporting
confidence: 61%
“…[6] Optical Spectra of ML(DPM) These spectra ( Figure 3 and Table 3) are characterized by intense bands due to πǞπ* electronic transitions localized on the planar system formed by the pyrrolizinido moiety and the adjacent chelate ring including the metal. The lowenergy portion of these spectra from the window centered at 500 nm is very similar to that of the corresponding MPc's spectra, except for an enhanced band intensity in the latter.…”
Section: X-ray Structure Of Nil(dpm)(pyr) 2 ⋅ 2 Pyrmentioning
confidence: 99%
“…No second pair of intense coupled B terms has been observed in the MCD spectra of D 2h complexes of phthalocyanines at the wavelength predicted for HFFM's R transition. 1 The authors do not make it entirely clear whether the partially oxidized CuPc species 3 that is referred to is a neutral complex or a cation radical. If it is a cation radical species, then their R transition could correspond to an intense broad B term at around 510 nm that is a characteristic feature observed within the MCD spectra of [MPc(-1)] + species.…”
mentioning
confidence: 99%
“…Neither of these proposals appears to have been taken into account the papers by Musselman and co-workers. [1][2][3] HFFM 1 state that the D 2h symmetry of their model compound allows them to observe spectral features hitherto unavailable in the case of D 4h complexes. It should be noted that MCD spectroscopy readily provides significantly more information for complexes of all symmetries than can be obtained from solidstate polarized specular reflectance spectra.…”
mentioning
confidence: 99%
“…The title anion, C 5 N 3 -C 4 N(CN) 2 -NH 2 Ϫ (LЈ, Scheme 1), which we synthesized for the first time from tetracyanoethylene (TCNE), 1 is the precursor of several bis(diiminotetracyanopyrrolizinato)metal() complexes ML 2 , 2-6 which are of considerable interest both in material science and in theoretical calculations. [7][8] With the aim of exploiting LЈ or its derivatives in practical applications, as in the construction of optochemical sensors, we have been studying their photometric properties, potentially useful for detecting species of environmental interest. We found that the following systems could be used as chemical sensors: (i) NaLЈ, embedded in sol-gel matrices, for Hg 2ϩ in water, 9 (ii) evaporated LH thin film, for gaseous ammonia 10 and (iii) NiL 2 , incorporated in a preformed, unplasticized polymer, for organic solvent vapors.…”
Section: Introductionmentioning
confidence: 99%